Development of Project Based-Flipped Classroom Textbooks in ICT-Based Learning Media Courses - Lita Sari Muchlis; Suharmon Suharmon; Asmendri Asmendri; Abdul Hamid; Feni Mardika; Uzmal Himmah (Institut Agama Islam Negeri Imam Bonjol Padang, 2026)
The rapid advancement of ICT in higher education necessitates learning resources that foster students’ autonomy and digital competence. However, existing materials often lack integration with constructivist models. This study aims to develop ICT-based teaching materials integrating Project-Based Learning and Flipped Classroom models to enhance students’ independent learning skills. Employing a Research and Development approach with the 4-D model, the study progressed through define, design, develop, and disseminate stages. The define phase identified learning needs at Universitas Islam Negeri Mahmud Yunus Batusangkar, while the design phase constructed a textbook prototype aligning Project-Based Learning syntax—such as project planning and implementation—with Flipped Classroom pre-class activities. During development, validity and practicality were assessed by subject-matter experts, media experts, and 15 graduate students using Aiken’s V analysis. Results indicated high validity, with instrument validity at 0.77, subject-matter expert validity at 0.82 (highly valid), and media expert validity at 0.75 (valid). Furthermore, student practicality reached 94.67% (highly practical). Limited dissemination confirmed the product's effectiveness in ICT-based learning media courses. It is concluded that this textbook is a valid and practical resource, effectively optimizing hybrid learning environments and supporting student-centered instruction in the digital era.